THE INFLUENCE OF SELF EXPRESSION, E-WOM, AND BRAND EQUITY TOWARD PURCHASE INTENTION ON SOCIAL MEDIA INSTAGRAM GOLDEN GEISHA - Aqsal, Ghulam Fadil (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Companies in the food sector have a very unique challenge where they need to do branding so that the company can be recognized. There are several important aspects that become indicators of the company in carrying out this strategy in practice. One of the strategies used is through social media marketing. This study aims to analyze the effect of the three components of marketing strategy on social media instagram golden geisha. This research was conducted using google forms and questionnaires distributed online. The research also requires 161 respondents, this research uses quantitative methods with data processing using PLS-SEM (smartpls). The results of this research test will provide answers to the results of the three components of activity, namely selfexpression has a positive effect on purchase intention, ewom has a positive effect on purchase intention and brand equity which has no positive effect on purchase intention.